Differences in analogical reasoning and oral language processes in bilingual primary students: quechua-castilian, shipibo-castilian and spanish speakers - Velarde Consoli, Esther (2019)
The objective of the present investigation was to establish whether there are differences in analogical reasoning and oral language processes in children from schools with education in Spanish with the influence of native languages versus Spanish speakers. 24 Socos students were evaluated; 30 from Huamanga, 30 from the Shipiba community and 30 Spanish speakers from Pachacútec. Significant differences were found in aspects such as phoneme discrimination, articulatory phonology, verbal memory, composition of sentences, description of actions, vocabulary, non-verbal intelligence, in favor of Pachacútec-Ventanilla students (those with the least linguistic interference), followed by students from Huamanga-Ayacucho; being the students of the rural community of Socos-Ayacucho. The same happened when the performance in non-verbal intelligence was compared. It is confirmed that exposing speakers of native languages to an education in Spanish it does not allow to properly construct its psycholinguistic structure or its analogical thinking.